Artificial Intelligence in Accounting Education and its Trends in Scopus: A Bibliometric Analysis - Rafael Romero-Carazas; Susana Irene Dávila-Fernández; Juan Britman Vallejos-Tafur; Freddy Antonio Ochoa-Tataje; Celfa Mónica Samaniego-Montoya; Julio Alberto Torres-Sánchez; María Soledad Porras-Roque; Antony Paul Espiritu-Martinez (Migration Letters, 2023)
Accounting education can greatly benefit from the incorporation of artificial intelligence, because it facilitates tasks and reduces the probability of human error. The aim of this study was to analyze the worldwide trends of scientific production in Scopus on artificial intelligence in accounting education during the period 2003-2023. It was a bibliometric analysis that defined the metrics of scientific production. The indicators were obtained from 110 documents chosen from the Scopus database using keywords in English ("artificial", "Intelligence", "Accounting", "Education"). The results show that between 2019 and 2022 there was a notable upturn in the number of papers published on the subject (62%). The highest scientific production rate is found in China (32.2%; n=38), and the highest publication rate is found in Ahlia University (n=4). The ACM International Conference Proceeding Series published 8 papers, while the most cited journal was Journal of Emerging Technologies in Accounting with 89 citations, with author Qasim, A. (n=2 papers) being the most cited (n=57). From the studies analyzed, it is concluded that the development of new technologies and the incorporation of these resources into a wide range of educational settings and pedagogical approaches, the field of AI in accounting education has grown, not only in terms of production and authorship, but also in terms of thematic diversity.